Markers of bone metabolism are associated in all-cause mortality in heart failure with reduced ejection fraction. (3rd October 2022) - Grubler, M; Fielder, L; Tscharre, M; Haiden, A; Pfeffer, M; Hartmann, A; Thianich, F; Roithinger, F X; Verheyen, N; Trummer, C; Theiler-Schwetz, V; Pilz, S; et al.
Abstract: Background: In patients with heart failure an increased risk of fracture-related mortality has been reported. A growing body of evidence suggests that, heart failure (HF) itself may be related to disturbances in bone metabolism, but the exact mechanism remains unclear. In patients with HF previous studies indicated a loss of renal function and alterations in bone micro-architecture, but the clinical relevance remains unclear. Purpose: We aimed to evaluate the association between markers of bone metabolism with mortality and pro-brain natriuretic peptide (proBNP) in patients with HF with reduced ejection fraction (HFrEF). Methods: We analysed participants of a prospective cohort study of patients referred to coronary angiography (CA). The baseline examination was performed at a tertiary care centre in Germany. Indications for CA were based on clinical routine. For the current analysis only patients with HFrEF were included. Patients were selected based on echocardiographic left ventricular (LV)-EF≤40%, symptoms of heart failure and elevated proBNP concentrations, as recommended by current clinical guidelines. We estimated the risk associated with parathyroid hormone (PTH), osteocalcin (OC), beta-crosslaps (βCL) and alkaline phosphatase (AP) and all-cause mortality using Cox proportional hazard models. Adjustments for demographic and clinical characteristics from the index hospital presentation were used as covariates. We included all individuals who had complete data for all variables in the study in our primary analysis. Additionally, we used linear regression analysis to investigate the correlation between proBNP and its association with PTH, OC, βCL and AP. Results: A total of 297 participants (63.9±9.9 years; 17.9% females) were included in the analysis. Median follow-up was 10 years. Median LV-EF was 35%, median New York Heart Association functional class was 2 (IQR=1–3), mean pulmonary capillary wedge pressure was 15.3±7.4 mmHg and median proBNP levels of 2282 (IQR 1875–3758) ng/ml. Participants had in 42.3% multi-vessel atherosclerotic CAD (with stenosis of ≥50% considered diagnostic) with 66.4% had a previous myocardial infarction. In multivariate cox proportionate hazard models OC, βCL and AP were statistically significant associated with an increased risk for all-cause mortality (hazard ratio (HR)=1.6 [95% CI 1.2–2.2], HR=1.8 [95% CI 1.1–2.9] and HR=2.1 [95% CI 1.5–2.9], respectively). In multivariate analysis proBNP was associated with PTH (β-coefficient = 0.076; P≤0.001), AP (β-coefficient = 0.125; P=0.001) and βCL (β-coefficient = 0.062; P=0.046), but not with osteocalcin (β-coefficient = −0.055; P=0.145). Conclusion: In patients with HFrEF markers of bone metabolism were significantly associated with mortality and proBNP concentrations. Future studies should focus on different aspects of bone metabolism, fracture rates and fracture related mortality in patients with different stages of heart failure. Funding Acknowledgement: Type of funding sources: None.